Synthesis of Substituted Cyclohexenones from the Condensation of Acetone with 1,3-Diaryl-2-propen-1-one - Abdul-Wahab (College of Education for Pure Sciences, 2010)
Abstract Claisen-Schmidt condensation had been used to prepare a series of 1,3-Diaryl-2-propen-1-one (1-10), under strong basic condations. The prepared chalcones (1-10) were condensed with acetone to afford the corresponding cyclohexenones (11-20). The structures of the final products had been identified in the light of valid spectral methods (U.V.,I.R.) as well as the typical identification tests .In addition, to the theoretical calculations of heat of formation H.F. and Steric energy S.E. were used to support the suggested reaction mechanism.